CCN6 improves hepatic steatosis, inflammation, and fibrosis in non‐alcoholic steatohepatitis. (12th October 2022) - Song, Yiran; Li, Chenyang; Luo, Yuxin; Guo, Jinbo; Kang, Yaxing; Yin, Fengrong; Ye, Lihong; Sun, Donglei; Yu, Jun; Zhang, Xiaolan
Abstract: Background and Aims: CCN6 is a secretory protein with functions of maintaining mitochondrial homeostasis and anti‐oxidative stress; and yet, whether it is involved in the pathogenesis of non‐alcoholic steatohepatitis (NASH) is still obscure. We investigated the role and mechanism of CCN6 in the development of NASH. Methods: Human liver tissue samples were collected to detect the expression profile of CCN6. High‐fat‐high‐cholesterol (HFHC) and methionine choline‐deficient (MCD) diet were applied to mice to establish NASH animal models. Liver‐specific overexpression of CCN6 was induced in mice by tail vein injection of adeno‐associated virus (AAV), and then the effect of CCN6 on the course of NASH was observed. Free fatty acid (FFA) was applied to HepG2 cells to construct the cell model of steatosis, and the effect of CCN6 was investigated by knocking down the expression of CCN6 through small interfering RNA (siRNA) transfection. Results: We found that CCN6 expression was significantly downregulated in the liver of NASH. We confirmed that liver‐specific overexpression of CCN6 significantly attenuated hepatic steatosis, inflammation response and fibrosis in NASH mice. Based on RNA‐seq analysis, we revealed that CCN6 significantly affected the MAPK pathway. Then, by interfering with apoptosis signal‐regulating kinase 1 (ASK1), we identified the ASK1/MAPK pathway pairs as the targets of CCN6 action. Conclusions: CCN6 protects against hepatic steatosis, inflammation response and fibrosis by inhibiting the activation of ASK1 along with its downstream MAPK signalling. CCN6 may be a potential therapeutic target for the treatment of NASH.